PENINGKATAN KAPABILITAS BENDAHARA PENERIMAAN DALAM PENGELOLAAN PENDAPATAN DAERAH KABUPATEN BONE - Alimuddin; Syarifuddin; Amiruddin; Muhammad Ashary (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Abstract. These community service activities are carried out in order to increase the capabilities of the Treasurer of Receipts - Regional Work Units in administering regional financial management so that they can carry out their roles in a professional, accountable and auditable manner. With the enhancement of the capabilities of the Receiving Treasurers, it is hoped that the financial management of Bone Regency can run well in accordance with statutory provisions, as well as in administration and reporting in line with the principles of government accounting standards. The method of implementation is done by way of lecturers and  tutorial. The results of the implementation of the activities show that the treasurers of SKPD recipients succeeded in administering the admissions treasurer well because this activity was related to their duties and authority as the treasurer of revenue.             Abstrak. Kegiatan pengabdian ini diselenggarakan dalam rangka meningkatkan kapabilitas Bendahara Penerimaan – Satuan Kerja Perangkat Daerah dalam menatausahakan pengelolaan keuangan daerah sehingga dapat menjalankan perannya secara professional, akuntabel dan auditable. Dengan peningkatan kapabilitas para Bendahara Penerimaan diharapkan pengelolaan keuangan Kabupaten Bone bisa berjalan dengan baik sesuai dengan ketentuan perundang-undangan, serta dalam penatausahaan dan pelaporan sejalan dengan prinsip standar akuntansi pemerintahan. Metode pelaksanaannya dilakukan dengan cara ceramah dan tutorial. Hasil pelaksanaan kegiatan menunjukkan bahwa para bendahara penerima SKPD berhasil melaksanakan penatausahaan bendahara penerimaan dengan baik karena kegiatan ini berkaitan dengan tugas dan wewenang mereka selaku bendahara penerimaan.